The influence of father involvement on academic resilience among late adolescents in Padang city - Sabrina Okta Fatonah; Devi Lusiria (Universitas Ahmad Dahlan, 2026)
Academic resilience is a critical capacity that enables adolescents to cope with academic challenges and sustain performance under pressure. Grounded in Social Support Theory, this study examines the association between father involvement and academic resilience among late adolescents. A total of 385 participants aged 16–18 years (78.7% female) completed validated measures of father involvement and academic resilience. Data were analyzed using simple linear regression. The findings revealed a significant positive association between father involvement and academic resilience (R = .637, R² = .405, F = 261.0, p < .001), indicating that higher levels of father involvement are associated with greater academic resilience. These results underscore the role of fathers as a salient source of social support that may enhance adolescents’ capacity to cope with academic demands. This study extends prior literature by highlighting the specific contribution of father involvement, rather than general parental support, within a non-Western adolescent context. Practically, the findings emphasize the importance of promoting father engagement in adolescents’ academic lives through family- and school-based initiatives to foster adaptive academic functioning.